KAJIAN SENSE OF PLACE TERHADAP USAHA PENINGKATAN PARIWISATA KOTA MEDAN PADA ISTANA MAIMUN KOTA MEDAN - Mulia, Endi Martha; Juliano, Thomas; Tandiah, Raymond; Wijaya, Michelle Olivia (LPPM ISTP, 2025)
Medan is a city with significant tourism potential, particularly through its preserved colonial and Deli Sultanate heritage buildings. One prominent example is Maimun Palace, which remains intact but has yet to attract an optimal number of visitors. This study aims to enhance Medan’s tourism potential by applying the sense of place theory, examined through circulation patterns, building image, and spatial comfort. A qualitative-descriptive method was employed, supported by interviews with selected respondents. The findings are expected to strengthen the role of tourism in preserving the city's historical architecture.